Art in the Hellenistic world - Stewart, Andrew F. (Cambridge, UK ; New York)
xiv, 357 sayfa
Keywords: “What was Hellenistic art, and what were its contexts, aims, achievements, and impact? This textbook introduces students to these questions and offers a series of answers to them. Its twelve chapters and two “focus“ sections examine Hellenistic sculpture, painting, luxury arts, and architecture. Thematically organized, spanning the three centuries from Alexander to Augustus, and ranging geographically from Italy to India and the Black Sea to Nubia, the book examines key monuments of Hellenistic art in relation to the great political, social, cultural, and intellectual issues of the time” --